Nonwoven production from agricultural okra wastes and investigation of their thermal conductivities - (:unkn) unknown (IOP PUBLISHING LTD, 2017)
Nowadays bio-based composite materials have been used in rising amounts and demanded widely in industrial uses, as they provide cost reduction and weight loss in the end use products. Agricultural cellulose based wastes can be a good alternative to synthetic fibers and can be used in natural fiber reinforced composite production, as there is a huge (more than 40 million tons) potential for natural cellulose production from agricultural wastes. Okra is one of the most grown vegetables around the world with stems left on the fields after harvest. When the similarity of mechanical properties of okra fibers with traditional bast fibers (flax, kenaf, hemp) are considered, from an economical and an environmental point of view this research emphasizes the potential of agricultural biomass for natural fiber production. In this study, okra stem wastes used for natural cellulosic fiber production and treated with 10% NaOH at 60 degrees C for 10, 20, 30 and 40 minutes. By alkali treatment, decrease in fiber diameter and weight, and increase in tensile strength and elongation % have been observed. Nonwoven production has been done from both the fibers with and without surface treatments. Thermal conductivity properties of both nonwovens have been investigated.
Keywords: NATURAL FIBER; COMPOSITES; SISAL; HEMP